Thermal dependence of austempering transformation kinetics of compacted graphite cast iron - Laneri, Karina Fabiana (2001)
The evolution of the relative fraction of high-carbon austenite with austempering time and temperature was analyzed in a compacted graphite (CG) cast iron (average composition, in wt pct: 3.40C, 2.8Si, 0.8Mn, 0.04Cu, 0.01P, and 0.02S) at five different austempering temperatures between 573 and 673 K. Samples were characterized by Mo¨ssbauer spectroscopy, hardness measurements, and optical microscopy. During the first stage of transformation, the kinetics parameters were determined using the Johnson–Mehl’s equation, and their dependence with temperature in the range from 573 to 673 K indicates that the transformation is governed by nucleation and growth processes. The balance between growth-rate kinetics and nucleation kinetics causes the kinetics parameter (k) to have a maximum at ’623 K of 3.9 3 1023 (s21 ). The evolution of the C content in the high-carbon austenite was found to be controlled by the volume diffusion of carbon atoms from the ferrite/austenite interface into austenite, with a dependence of t 0.4060.05 on the austempering time (t).